Business Continuity: Application of The Value of Catur Purusa Artha and Product Innovation in Holding Company of BUMDes - Ni Luh De Erik Trisnawati; Riana Dewi Kartika; Ni Luh Sri Kasih (International Journal of Social Science and Business, 2021)
Business management based on the local culture of catur purusa artha by making dharma (truth) the basis for carrying out all its activities, creating internal conditions in the form of a conducive work climate. This study aims to examine the application of the value of catur purusa artha and product innovation in creating business continuity. The research population is all active BUMDes in Buleleng Regency. Sampling in this study using random sampling technique in order to obtain as many as 92 observational data. The data analysis technique used in this study was the Component based SEM, Partial Least Square (PLS) analysis method. The results showed that the value of Catur purusa artha had a significant effect on product innovation. Product innovation has a significant effect on business continuity and the value of catur purusa artha affects business continuity through product innovation. This study also found that business management based on the local culture of Catur Purusa Artha by making dharma (truth), as the basis for carrying out all its activities, creates internal conditions in the form of a conducive work climate. BUMDes managers, including all employees who work comfortably based on dharma, have actually come up with creative ideas in product development. Management of business units based on dharma provides awareness to act in the truth and creates an environment that minimizes abuse of authority, including various other forms of wrongdoing. The concept of dharma also emphasizes to always provide good service to customers.